Oral Lipomas- Rare Conditions in Oral Cavity, A Review - N.Anitha1 , Sudakshina Mukherjee2 , N. Aravindha Babu3 , L.Malathi4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oral lipomas are rare benign lesion. Though soft tissue lipomas are not uncommon oral lipomas are relativelyless in number. Mostly goes asymptomatic and are rarely comes to dental professionals either by accidentalfindings or complaint from a patient due to aesthetic reasons. Various histological variant of lipomas arethere but most common is classical lipoma followed by fibrolipoma. Prognosis of these benign intraorallesions is good. In this review article we will discuss about etiology, theories regarding pathogenesis, clinicalfeatures, Histological variant of Oral Lipomas.